Razvitie nachnykh issledovanii na fakul'tete fizicheskoi kul'tury Kazanskogo gosudarstvennogo pedagogicheskogo universitete - Abzalov, R. A.; Sitdikov, F. G. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The article is devoted to the history of scientific researches' development at the physical culture faculty of the Kazan state pedagogical university. The authors represent the retrospective analysis of the scientific researches' directions at the faculty: the problems of physical culture's physiology (O.D. Kurmayev, F.G., Sitdikov, R.A. Abzalov) the problems of sports pedagogy (Ya.I. Hanbikov, I.A., Polovnikova) the problems of physical culture's psychology (E.N. Klimova, A.O. Prohorov) the theoretical fundamentals of physical culture (R.A. Abzalov, F.G. Sitdikov, R.H. Yarullin) the problems of the ecology (R.A. Abzalov, .A.I. Ziyatdinova).